2016
DOI: 10.21832/isaacs6848
|View full text |Cite
|
Sign up to set email alerts
|

Second Language Pronunciation Assessment

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms This series brings together titles dealing with a variety of aspects of language acquisition and processing in situations where a language or languages other than the native language is involved. Second language is thus interpreted in its broadest possible sense. The volumes included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 253 publications
(356 reference statements)
0
5
0
Order By: Relevance
“…In their study on the L2 phonology of English-speaking learners of Spanish and Spanish-speaking learners of English, found that learners with higher inhibitory skill were more accurate at perceiving L2 vowels and more accurate at producing L2 consonants. However, Mora and Darcy (2016) found no relationship between inhibitory control and L2 pronunciation accuracy for learners of English who were L1 Spanish speakers or L1 Spanish-L1 Catalan bilinguals. In a similar study, did find that stronger inhibitory control was related to more accurate perception by L1 Spanish learners of English, although not if they were L1 Spanish-L1 Catalan bilinguals.…”
Section: Inhibitory Controlmentioning
confidence: 73%
See 3 more Smart Citations
“…In their study on the L2 phonology of English-speaking learners of Spanish and Spanish-speaking learners of English, found that learners with higher inhibitory skill were more accurate at perceiving L2 vowels and more accurate at producing L2 consonants. However, Mora and Darcy (2016) found no relationship between inhibitory control and L2 pronunciation accuracy for learners of English who were L1 Spanish speakers or L1 Spanish-L1 Catalan bilinguals. In a similar study, did find that stronger inhibitory control was related to more accurate perception by L1 Spanish learners of English, although not if they were L1 Spanish-L1 Catalan bilinguals.…”
Section: Inhibitory Controlmentioning
confidence: 73%
“…He found a moderate positive correlation between the two, such that higher PSTM was related to higher pronunciation ratings from native Spanish speakers. A positive relationship between PSTM and pronunciation accuracy was also evidenced by Mora and Darcy (2016) for Spanish-speaking learners of English.…”
Section: Phonological Short-term Memorymentioning
confidence: 74%
See 2 more Smart Citations
“…This volume does share some common focuses with Isaacs and Trofimovich (2016), such as the discussion about constructs in pronunciation, the native speaker norm and ELF, factors influencing rater/listener judgments of pronunciation, etc. But it is distinctive from the latter in that while the latter includes technology and automated scoring in future direction, this volume has detailed discussion about this issue.…”
mentioning
confidence: 99%